Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
5(x – 4) + 3x – 9x = 6 – (2x + 5) + 8x
step1:- 5x - 20 + 3x - 9x = 6 - 2x - 5 + 8x
step2:- 5x + 3x - 9x - 20 = 8x - 2x + 6 - 5
-x - 20 = 6x + 1
stp 3
-20 = 7x + 1
step 4
-21 = 7x
divide both sides by 7:-
-3 = x
thats the solution x = -3
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.